A human-phantom coupling experiment and a dispersive simulation model for investigating the variation of dielectric properties of biological tissues. (1st June 2015) - Gomez-Tames, Jose; Fukuhara, Yuto; He, Siyu; Saito, Kazuyuki; Ito, Koichi; Yu, Wenwei
Abstract: Variation of the dielectric properties of tissues could happen due to aging, moisture of the skin, muscle denervation, and variation of blood flow by temperature. Several studies used burst-modulated alternating stimulation to improve activation and comfort by reducing tissue impedance as a possible mechanism to generate muscle activation with less energy. The study of the effect of dielectric properties of biological tissues in nerve activation presents a fundamental problem, which is the difficulty of systematically changing the morphological factors and dielectric properties of the subjects under study. We tackle this problem by using a simulation and an experimental study. The experimental study is a novel method that combines a fat tissue-equivalent phantom, with known and adjustable dielectric properties, with the human thigh. In this way, the dispersion of the tissue under study could be modified to observe its effects systematically in muscle activation. We observed that, to generate a given amount of muscle or nerve activation under conditions of decreased impedance, the magnitude of the current needs to be increased while the magnitude of the voltage needs to be decreased. Highlights: The effect of tissue dispersion was studied using current and voltage stimulations. A novel method was proposed to systematically change the dispersion of the tissues. Current needs to be increased to generate activation under decreased impedance. Voltage needs to be decreased to generate activation under decreased impedance. Optimal pulse duration also depends on the pulse stimulation.